Places in Knots : Remoteness and Connectivity in the Himalayas and Beyond - Saxer, Martin, 1971- (Book collections on Project MUSE., 2022)
"A study on Himalayan communities from northern Nepal, their transnational ventures, and the ties between the places they inhabit"--